Challenges of public institutional communication during the COVID-19 pandemic: A qualitative study.: Presenter(s): Nicola Diviani, Swiss Paraplegic Research / University of Lucerne, Switzerland. (April 2023) - Fiordelli, Maddalena; Rubinelli, Sara
Abstract : Background: With the spread of the COVID-19 pandemic, health institutions worldwide were urged to inform the public daily about an uncertain epidemiological situation and the introduction of new measures. They had to do so in an infodemic context, i.e., a context with too much information, including false or misleading information. This study aims at identifying the main challenges encountered by Swiss health institutions in their communication with the public during the first two waves of the COVID-19 pandemic. Methods: In-depth qualitative interviews with representatives of key health institutions (N = 46) across Switzerland were conducted in late 2020. Participants were asked to discuss the primary issues encountered when informing the public and how these were addressed. Interviews were analyzed using thematic analysis techniques. Findings: Internally, institutions often had to deal with rigid organizational structures that left little maneuvering space, for example, when trying out new communication channels or modalities (e.g., on social media). Externally, communication was often hindered by a lack of trust in institutions and low health/scientific literacy in the public. Finally, institutions had to face environmental challenges, in primis the spread of mis- and disinformation in news and social media. The ability to listen and respond to the demands of the public, flexibility, creativity, and the establishment of synergies and collaborations with other key actors in the public arena (e.g., the news media) were reported as critical factors in facilitating communication. Discussion: To prepare for future pandemics, institutions need to implement mechanisms that give space for experimenting and innovation. This is particularly important as communication modalities are constantly evolving, and there is a risk that parts of the population are left out of the discussion. At the population level, our Findings: underline the need to systematically invest in building trust in institutions and promoting health and scientific literacy.